KAJIAN KARAKTERISTIK KIMIA, FISIK, DAN SENSORIS KERIPIK SIMULASI BERBAHAN DASAR IKAN BANDENG (Chanos chanos) DAN TEPUNG KACANG HIJAU (Vigna radiata L.) SEBAGAI MAKANAN RINGAN SUMBER PROTEIN - Arrosyid, Fadlilah; Prabawa, Sigit; Yudhistira, Bara; Atmaka, Windi (Universitas Sebelas Maret (UNS), 2018)
Diversification of food products one of which can be applied to snacks.. One type of snack that is quitesuccessful in the market is the chips. To improve the value of the nutritive value of these chips is by makingsimulation chips. Based on protein content of milkfish and mung beans are high then used as raw material forthe manufacture of simulated chips.This study aims to determine the best simulation of milkfish and mung beansflour based on characteristics of chemical, physical, and sensory. Experimental design using in this researchwas Completely Randomized Design (CRD) with one factor, that was ratio variation of milkfish and mung beanflour. Based on the results of chemical, physical, and sensory analyzes obtained were analyzed statistically byusing one way ANOVA method, if there was a difference, it was followed with significance test using Duncan’sMultiple Range Test (DMRT) at significance level of α = 0,05.Based on the results of the study showed the best formulation results on F3 (20% milled milkfish meat +80% mung beans flour). Result of chemical analysis of simulation chips at F3 that is moisture content 3,53% wb;ash content 3,44% db, fat content 25,78% db; protein content 18,84% db; carbohydrate content 51,93% db;FFA content of 0.45% db; crude fiber content 5,57% db; and total calories 527.17 kcal / 100gram. Result ofphysical analysis of simulation chips on F3 that is hardness 7,95 N and wholeness 92,97%. While on the sensoryanalysis the highest F3 value on parameters of color, texture, and overall.